ANALISIS PRODUKTIVITAS PRODUKSI MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) DI PT PABRIK CAT TUNGGAL DJAJA INDAH - Nadya Natasya; Erni Puspanantasari Putri (Journal of Industrial Engineering & Technology Innovation, 2026)
This study aims to measure and analyze the productivity level of water-based paint production at PT Pabrik Cat Tunggal Djaja Indah using the Objective Matrix (OMAX), Analytical Hierarchy Process (AHP), and Root Cause Analysis (RCA) methods. The research problem is based on the failure to achieve the water-based paint production target in several months during the period from July to December 2025. The OMAX method was used to measure productivity based on seven ratios, namely raw material utilization, working hours, production effectiveness, product quality, machine operating time, labor, and electrical energy. AHP was used to determine the priority weight of each criterion, while RCA through a Fishbone Diagram was used to identify the root causes of low productivity. The results showed that production productivity fluctuated, with the highest value recorded in September at 5.4559 and the lowest value recorded in July at 1.9783. Factors affecting low productivity included inefficient raw material utilization, machine downtime, defective products, suboptimal labor utilization, and unstable electrical energy consumption. The proposed improvements include raw material supervision, implementation of preventive maintenance, improvement of operator skills, production quality control, SOP evaluation, and optimization of electrical energy use. The findings of this study are expected to serve as a basis for continuous improvement in water-based paint production productivity.